A finite element model for seismic response analysis of vertically-damped rocking-columns. (15th September 2020) - Aghagholizadeh, Mehrdad
Abstract: This paper investigates finite-element modeling of a vertically damped free-standing rocking column. The paper first derives the nonlinear equation of motion for the coupled system and then compares the analytical solution with finite-element model. Finite-element model is being produced using open source framework named OpenSees. The rocking surface is modeled using zero-length fiber cross-section element and the dampers are modeled with two node link elements. In order to simulate energy dissipation during the rocking motion Hilber-Hughes-Taylor numerical dissipative time step integration is being adopted. The paper also compares two types of hysteretic and viscous damping devices and it shows that the viscous damping behavior is favorable when it is used along with a rocking block. The results of analytical model of a rigid block with viscous dampers in MATLAB is then compared with OpenSees model and the paper concludes that the finite-element model compares satisfactory with the analytical model.